Neuropathy following intramuscular injections: a clinical and neurophysiological study from a tertiary care centre in Pakistan - Tariq, Adnan; Ayesha Aslam; Awan, Nukhbatullah; Bano, Safia; Numan, Ahsan (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the clinical and neurophysiological profile of peripheral nerve injuries in patients following intramuscular injections. Method: The descriptive, cross-sectional study was conducted at the Department of Neurology, Mayo Hospital, Lahore, Pakistan, from July 2019 to January 2021, and comprised adult patients of either gender with isolated peripheral nerve injuries following intramuscular injections. Nerve conduction studies were performed for each patient. Data was analysed using SPSS 26. Results: Of the 99 patients, 59(59.6%) were males and 40(40.4%) were females. The mean age was 26.7+/-18.1 years, 34(34.3%) patients were under weight and 78(78.8%) were either illiterate or had low literacy level. Radial nerve was involved in 56(56.6%) cases, followed by sciatic in 39(39.4%) and axillary nerve 4(4.04%). Overall, 14(14.14%) injection had been administered by doctors, while the other 85(85.85%) were given by paramadics. Marked reduction in compound muscle action potential 72(72.7%) and sensory nerve action potential 82(82.8%) was noted, while re-innervation was seen in 78(78.7%). Conclusion: Intramuscular nerve injuries can be greatly minimised by spreading awareness regarding safe injection techniques and strict implementation of standard operating procedures in hospitals and clinics. Key Words: Intramuscular injections, (M, Peripheral nerve injuries, PNI, Neuropathy.